2D Frustrated Magnets: Reentrant Spin Glass and Large Coercive Field Observed in a Spin Integer Dimerized Honeycomb Lattice (Adv. Funct. Mater. 1/2021). (4th January 2021) - Zhai, Yuan‐Qi; Deng, Yi‐Fei; Fu, Zhendong; Feng, Erxi; Su, Yixi; Shiga, Takuya; Oshio, Hiroki; Zheng, Yan‐Zhen
Abstract : In article number 2004744, Zhendong Fu, Yan‐Zhen Zheng, and co‐workers report a van der Waals 2D magnetic material bearing a spin‐integer dimerized honeycomb lattice. This material can be prepared down to ten layers (13 nm in thickness) and exhibits a reentrant spin glass behavior with very hard magnetic hysteresis. Owing to the dedicated chemical design, this work successfully combines topological spin‐frustration in 2D magnets.